The longest day - Ryan, Cornelius; Annakin, Key; Marton, Andrew; Wicki, Bernhard; Twentieth Century Fox.; Darryl F. Zanuck Productions (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Complete story of the D-Day landings at Normandy through the eyes of all its participants.
Title from container.
Casts: John Wayne, Robert Mitchum, Henry Fonda, Eddie Albert, Richard Burton, Sean Connery, Peter Lawford, Rod Steiger, Stuart Whitman, Robert Ryan, Edmond O'Brien, Curt Jürgens.
English, dubbed French or dubbed Spanish dialogue, English or Spanish subtitles.
Keywords: World War, 1939-1945 -- Campaigns -- France -- Normandy -- Drama; Generals -- Drama; Parachute troops -- Drama; Soldiers -- Drama